Re(I)novation of Supply Chain Management for the Improvement of Business Performance in Shallot Commodities - Rahmawati, Lia Dwi; Usman (International Publisher, 2024)
The poor condition of the Shallot Commodity Supply Chain can be observed from the fluctuations from upstream to downstream, due to the dynamic changes in the demand and supply quantities up to the distribution channel amounts. The (Re)innovation of Shallot Supply Chain Management is an innovation from the aspects of Partnership, Contractual Agreements, Transaction Systems, and Government Support. The objective of this research is to analyze the shallot supply chain model using the Food Supply Chain Framework (FSCN) approach. The method used is qualitative descriptive research, describing the behavior of the actors in the supply chain. This research was conducted from August 2022 to January 2023, using primary data collected through in-depth interviews with 152 respondents, shallot farmers in 5 regencies in Central Java. The sampling technique used is purposive sampling. The results of the study on the business performance of shallot commodities in forming an efficient supply chain management require criteria to improve partnerships, indicating that its marketing performance is already running well. Shallot commodity business actors are engaged in partnerships to monitor and evaluate marketing effectiveness periodically. This research has successfully enhanced the capabilities of the resources of the supply chain actors, making them more efficient and effective in transforming the agricultural sector.